PERAN PRAMUKA SEBAGAI ORGANISASI EKSTRAKURIKULER DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI PANGKALAN SMA NEGERI 2 MALUKU TENGAH - Ali Holle, Muhammad; Toisuta, Sitna Rahel (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2025)
The Scout Movement itself functions as an organizer of non-formal education outside of school and outside the family. This education is a forum for fostering and developing young people with special characteristics. Its special characteristics are the application of the Basic Principles of Scouting and Scouting Methods and the Among System in education carried out by the Scout Movement. In addition to being an organizer of non-formal education, the Scout Movement also functions as a forum to achieve the goals of the Scout Movement. Scouts as an extracurricular organization in educational units have a very positive impact on Indonesian education where the goals of extracurricular activities for students can support their development into better individuals, encourage independent, diligent and skilled behavior, can develop their potential through cognitive, affective and psychomotor aspects. Character formation through scouting activities in order to foster, improve, or form a person's nature, character, morals, and manners. as well as human behavioral values ​​related to God Almighty, oneself, fellow human beings, the environment, and nationality which are manifested in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, manners, culture, and customs. The type of research conducted is descriptive qualitative, with the approach taken being an educational, sociological and normative approach. The data collection method in the form of structured interviews, observation of activities, and supporting documents in the data collection process focuses on extracurricular activities in forming the character of Discipline, Creative Character and Independent Character in Scouting Activities. The results of the study show that: 1) The Disciplined Character instilled by scout members in the Nusa Ina Scout Group is time discipline, discipline in following the assembly and discipline in complying with the rules and regulations that have been made in the Scout Group. 2) The Creative Character carried out in the Nusa Ina Scout Group is learning while doing, being able to design activities both in the campsite and in the open air, and being creative in designing fun and enjoyable learning. 3) The Independent Character carried out in the Nusa Ina Scout Group is being able to carry out the Ambalan Deliberation, being able to make decisions, and being able to organize camping activities and prepare activity schedules professionally.